2012
DOI: 10.1007/s11999-012-2492-3
|View full text |Cite
|
Sign up to set email alerts
|

What is the Best Way to Apply the Spurling Test for Cervical Radiculopathy?

Abstract: Background A diagnosis of cervical radiculopathy is based largely on clinical examination, including provocative testing. The most common maneuver was described in 1944 by Spurling and Scoville. Since then, several modifications of the original maneuver have been proposed to improve its value in the diagnosis of cervical radiculopathy. Questions/Purposes We assessed the ability of six known variations of the Spurling test to reproduce the complaints of patients diagnosed with cervical radiculopathy. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 18 publications
0
9
2
Order By: Relevance
“…This maneuver, even without axial compression, is a reliable provocative test in the diagnosis of cervical radiculopathy. 24 The shoulder abduction test for cervical radiculopathy is well-suited for telemedicine. 25 Patients are instructed to abduct their shoulder and hold their arm above their head.…”
Section: Cervical Spinementioning
confidence: 99%
“…This maneuver, even without axial compression, is a reliable provocative test in the diagnosis of cervical radiculopathy. 24 The shoulder abduction test for cervical radiculopathy is well-suited for telemedicine. 25 Patients are instructed to abduct their shoulder and hold their arm above their head.…”
Section: Cervical Spinementioning
confidence: 99%
“…Combining the results of these three studies, it appears that lateral rotation of the neck decreases the sensitivity of the test for the detection of cervical radiculopathy. This rationale is supported by Anekstein et al [ 11 ] who found the greatest sensitivity with the combination of lateral bending and extension without rotation. Thus, we prefer to perform the Spurling's test in neutral rotation to improve diagnostic effi cacy.…”
Section: Spurling's Testmentioning
confidence: 78%
“… 15 , 16 A Spurling test was also performed to rule out the presence of cervical radiculopathy. 17 , 18 …”
Section: Participants and Methodsmentioning
confidence: 99%